2012
DOI: 10.1103/physrevlett.108.245002
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Quasi-Isodynamic Stellarators against Trapped-Particle Instabilities

Abstract: It is shown that in perfectly quasi-isodynamic stellarators, trapped particles with a bounce frequency much higher than the frequency of the instability are stabilizing in the electrostatic and collisionless limit. The collisionless trapped-particle instability is therefore stable as well as the ordinary electron-density-gradient-driven trapped-electron mode. This result follows from the energy balance of electrostatic instabilities and is thus independent of all other details of the magnetic geometry.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(123 citation statements)
references
References 16 publications
11
112
0
Order By: Relevance
“…Since it still holds for the electrons, these act stabilising and any instability must draw its energy from the ions. This result has earlier been found through linear stability analysis by Proll et al (2012), but is here found to be true even for large perturbations.…”
Section: Discussionsupporting
confidence: 86%
“…Since it still holds for the electrons, these act stabilising and any instability must draw its energy from the ions. This result has earlier been found through linear stability analysis by Proll et al (2012), but is here found to be true even for large perturbations.…”
Section: Discussionsupporting
confidence: 86%
“…As we have just seen, the simplest form of the TEM is not present in such configurations, and in Ref. [61] it is shown from basic energy considerations that any particle species with k v T a ≫ ω and 0 < η a < 2/3 exerts a stabilising influence on arbitrary electrostatic, collisionless instabilities. Physically, the point is that, because J is an adiabatic invariant, if an instability with ωτ b ≪ 1 results in the radial movement ∆ψ of a particle, then…”
Section: Analytical Considerationsmentioning
confidence: 99%
“…If the electrons are also treated gyrokinetically, recent analytical theory [27][28][29] and numerical results [30] show that densitygradient-driven instabilities are much more stable in many stellarators than in tokamaks. The reason is that these modes are caused by electrons being magnetically trapped in regions of bad curvature.…”
mentioning
confidence: 99%